2015
DOI: 10.1158/1535-7163.targ-15-b85
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B85: EZH2 plays a critical role in B-cell maturation and in non-Hodgkin's lymphoma: Interplay between EZH2 function and B-cell activation

Abstract: The EZH2 inhibitor tazemetostat (EPZ-6438) is emerging as a promising therapeutic agent for the treatment of non-Hodgkin's Lymphoma (NHL). A significant body of work has now demonstrated in vitro and in vivo effects of EZH2 inhibition in preclinical models of lymphoma, in addition to objective clinical responses in early human trials. While EZH2 gain-of-function mutations clearly contribute to lymphomagenesis, patients with lymphomas harboring wild-type EZH2 also show responses to tazemetostat. This suggests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For example, in the mammalian B-cell life cycle, an unnatural trimethylated state of H3K27 arrests the germinal center in the dark zone, preventing differentiation and resulting in aberrant proliferation as opposed to transition to the light zone and either further B-cell maturation, if needed, or alternative apoptosis in a healthy immune system [151]. Preclinically, it has been observed that treatment with EZH2 inhibitors leads to enrichment of B-cell maturation gene sets, suggesting that EZH2 inhibition could result in a cancer cell differentiation event that would lead, in time, to selective apoptosis [152]. One of the advantages of a selective EZH2 inhibitor is that only cells with a genetic addiction to EZH2 activity should be affected by global reduction in H3K27me3 which could enable dosing of therapeutics up to efficacious exposures without deleterious side effects from general cellular toxicity.…”
Section: Target Introductionmentioning
confidence: 99%
“…For example, in the mammalian B-cell life cycle, an unnatural trimethylated state of H3K27 arrests the germinal center in the dark zone, preventing differentiation and resulting in aberrant proliferation as opposed to transition to the light zone and either further B-cell maturation, if needed, or alternative apoptosis in a healthy immune system [151]. Preclinically, it has been observed that treatment with EZH2 inhibitors leads to enrichment of B-cell maturation gene sets, suggesting that EZH2 inhibition could result in a cancer cell differentiation event that would lead, in time, to selective apoptosis [152]. One of the advantages of a selective EZH2 inhibitor is that only cells with a genetic addiction to EZH2 activity should be affected by global reduction in H3K27me3 which could enable dosing of therapeutics up to efficacious exposures without deleterious side effects from general cellular toxicity.…”
Section: Target Introductionmentioning
confidence: 99%
“…Some studies of combinations between modulators of CMPs of distinct modalities have, however, been reported; most notably, preclinical and clinical studies of combinations of HDAC inhibitors and DNA hypomethylating agents 4 and preclinical studies of DNA hypomethylating agents in combination with inhibitors of the PMTs DOT1L 5 and EZH2 6 have revealed striking synergies in reducing tumor burden. Drug synergy resulting from combining CMP modulators of differing modalities seems to make intuitive sense.…”
mentioning
confidence: 99%
“…7 Likewise, studies in B-cell lymphoma models have demonstrated synergy between the EZH2 inhibitor tazemetostat and modulators of several distinct biochemical pathways. 6 Synergy was seen with B-cell signal transduction kinase inhibitors, BCl2 and BCl6 antagonists, 6 and, perhaps most surprisingly, corticosteroid agonists of the glucocorticoid receptor. 8 While many of these biochemical pathways ultimately lead to changes in gene transcription, the synergies seen between these various pathways and CMP modulators reveal hitherto unrecognized biological connections that may aid in our understanding of pathogenesis and that may be exploited for greater clinical activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations